The human and natural factors causing economic and social crises in Andalusia 94-422 AH / 712-1031 CE - قرحيلي نبيل (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The Andalusian era was distinguished as an era of prosperity and progress, although many crises suffered from it, its factors and reasons varied. Therefore, this search was made for natural and human factors and their impact on the economy in Andalusia, and also what affected Andalusian society as well. The natural factors diversified and were beyond the control of humans and they have a direct impact on the lives of peoples, including droughts, droughts, earthquakes, floods and hurricanes. Locusts that directly threaten the economic situation are added to them, and how they led to the occurrence of famines, epidemics and the deterioration of the general conditions in Andalusia. As for the human factors, including the temptations that occurred in Andalusia between the Arabs and the Berbers on the one hand and between the Arabs themselves on the other hand, and also the external wars between the Arabs in Andalusia and the Franks, in addition to the Fatimid danger and the Abbasid danger, in addition to the human factors the life of luxury and opulence experienced by the Umayyad caliphs in Andalusia , And the principle of inheriting the throne, which was the reason for the incompetence to reach power. And try to identify the deteriorating conditions that have caused the economy and society in Andalusia.